Application of PVP VA 64 and Poloxamer 188/407 in Solid Dispersion Technology for Improving Solubility of Valsartan - Cahyani, Sulastari; Saifullah Sulaiman, Teuku Nanda; Laksitorini, Marlyn Dian (UI Scholars Hub, 2024)
Valsartan, Biopharmaceutical Classification System (BCS) class II drug, exhibits pH-dependent solubility in the gastrointestinal tract, which increases at pH levels above 5. Its low solubility results in a bioavailability of only 23%, necessitating efforts to enhance it. This study aims to improve the solubility of valsartan using a solid dispersion system. Polyvinylpyrrolidone/vinyl acetate 64 (PVP VA 64), a hydrophilic polymer, was incorporated to inhibit the recrystallization of valsartan, while poloxamer 188 and poloxamer 407, used as surfactants, aimed to enhance valsartan’s solubility and intrinsic dissolution rate. Valsartan solid dispersions were prepared using the spray drying method, and the optimal formulation was determined using the Simplex Lattice Design (SLD). The composition of PVP VA 64, poloxamer 188, and poloxamer 407 were optimized factors, while saturated solubility, melting point, and intrinsic dissolution rate at pH 1.2 and 4.5 as optimized responses. The valsartan solid dispersions were characterized using Differential Scanning Calorimetry (DSC), Fourier Transform Infrared (FTIR) spectroscopy, Powder X-Ray Diffractometry (PXRD), and Scanning Electron Microscopy (SEM). The optimal composition of the valsartan solid dispersion was 40 mg of valsartan, 100 mg of PVP VA 64, 10 mg of poloxamer 188, and 30 mg of poloxamer 407. The results indicated that the solubility of valsartan solid dispersion was 27 times higher than that of the pure drug. Furthermore, the intrinsic dissolution rate of the valsartan solid dispersion at pH 1.2 and 4.5 exceeded that of pure valsartan.